Answer:
12 becayse u mulitigigivuvuu
Complete Question
The complete question is shown on the first uploaded image
Answer:
Based on the result of his test , Thomas should fail to reject null hypothesis at a significance level of 0.01. Thomas sufficient evidence to conclude that the proportion of households without children in the set of all future samples reached by phone is not equal to the proportion of households without children in the population of all households.
Step-by-step explanation:
From the question we see that the p-value is greater than the level of significance (0.01 )so we fail to reject the null hypothesis.
This means that Thomas has sufficient evidence to conclude that the proportion of households without children in the set of all future samples reached by phone is not equal to the proportion of households without children in the population of all households.
Answer:
Step-by-step explanation:
Remark
Let the shorter base = x
Let the longer base = 3x
h = 5
Area = 60
Formula
Area = (b1 + b2)*h /2
Solution
60 = (x + 3x)*5 / 2 Multiply both sides by 2
2*60 = (x + 3x)*5 Combine like terms
120 = 4x *5
120 = 20x Divide by 20
120/20 = x
x = 6
Therefore the two bases are
x = 6
3x = 18
Answer:
C
Step-by-step explanation:
Answer:
x=-3
Step-by-step explanation:
(3x-15)/2 = 4x
Multiply each side by 2
(3x-15)/2 *2= 4x*2
3x-15 = 8x
Subtract 3x from each side
3x-15-3x = 8x-3x
-15 = 5x
Divide each side by 5
-15/5 = 5x/5
-3 =x
Answer:
X=-3
Step-by-step explanation:
10xy=W
Answer:
x=W/10y
Step-by-step explanation:
9514 1404 393
Answer:
2a. (x, y) = (2, 2)
2b. (x, y) = (3, -1)
3. -5, 3, y, 5, 1
Step-by-step explanation:
The first equation defines an expression for x, so it is convenient to use that to substitute for x in the second equation.
2(3y-4) -y = 2 . . . . . substitute for x
6y -8 -y = 2 . . . . . . eliminate parentheses
5y = 10 . . . . . . . . . add 8, collect terms
y = 2 . . . . . . . . . . divide by 5
x = 3(2) -4 = 2 . . . find x using the first equation
The solution is (x, y) = (2, 2).
__
Add 3 times the second equation to the first.
(3x +2y) +3(-x +y) = (7) +3(-4)
5y = -5 . . . . . simplify
y = -1 . . . . . . . divide by 5
x = y +4 = -1 +4 = 3 . . . . rearrange the second equation
The solution is (x, y) = (3, -1).
__
The slope of this equation is -5 [the x-coefficient]. I would start at +3 [the y-intercept] on the y axis and then drop down 5 and run over 1 .
[The slope is the ratio of rise to run. A slope of -5 means the "rise" is a drop of 5 for each "run" of 1 unit to the right.]
7x − 5, x ≤ −5
−x2, x > −5
.
Find
f(−1), f(−5), and f(−6)
Answer:
EZ
Step-by-step explanation:
EZ